Hepatotoxicity during anti-cancer chemotherapy - Piątkowska, Magdalena; Pogorzała, Monika; Dębski, Robert; Styczyński, Jan (Contemporary Oncology/Współczesna Onkologia, 2008)
Background: Hepatotoxicity is defined as injury to the liver that is associated with impaired liver function caused by exposure to a drug or another noninfectious agent. It is one of the most frequent direct side effects of chemotherapy. Cytotoxic drugs which cause hepatotoxicity are: methotrexate, mercaptopurine, cytarabine, 5-fluorouracil, L-asparaginase, cyclophosphamide, busulfan, dacarbazine, mitomycin, thioguanine, mitramycin, etoposide, nitrosourea derivatives (carmustine, lomustine), cisplatin; while actinomycin, doxorubicin, vincristine and vinblastine cause liver injury less often. Objective: Analysis of grade of hepatotoxicity in children treated for neoplastic diseases. Material and methods: The study group consisted of 237 patients with cancer. Concentration of total serum bilirubin, activity of glutamyl pyruvic transaminase (GPT, AlAT) and glutamyl oxaloacetic transaminase (GOT, AspAT) was analyzed. Common toxicity criteria for adverse events CTCAE v3.0 was used for grading the hepatotoxicity. Results: Biochemical symptoms of hepatotoxicity were observed in 59.4% of children with cancer, including 24.9% of patients with grade III/IV of toxicity, which prevented continuation of chemotherapy. Hepatotoxicity of grade III/IV was most often observed in children treated for acute lymphoblastic leukaemia and non-Hodgkin’s lymphoma, while it was not observed in patients with Hodgkin’s disease, Langerhans cell histiocytosis or chronic myeloid leukaemia. Conclusions: Hepatotoxicity is a frequent adverse event of chemotherapy in children. Increased activity of glutamyl pyruvic transaminase (GPT, AlAT) is the main biochemical feature of direct liver injury.